2020
DOI: 10.1186/s13643-020-01458-8
|View full text |Cite
|
Sign up to set email alerts
|

Zolpidem reduces pain intensity postoperatively: a systematic review and meta-analysis of the effect of hypnotic medicines on post-operative pain intensity

Abstract: Background: This systematic review aimed to investigate whether the administration of hypnotic medicines, zdrugs, melatonin or benzodiazepines, reduced pain intensity postoperatively. Methods: Medline, Embase, Cinahl, Psych info, Central and PubMed databases were searched, from inception to February 2020 to identify relevant trials. The search was extended, post hoc, to include meta-Register of Controlled Trials, the Web of Science and the conference booklets for the 14th, 15th, and 16th International Associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…We too were interested in understanding how sleep management might be helpful for people with pain and synthesized the evidence available to investigate the effect of hypnotic medicines at reducing pain intensity postoperatively (O'Hagan et al, 2020). The systematic review results show that there was moderate-quality evidence that the hypnotic medicine zolpidem, a z-drug, administered in the postoperative period had an analgesic effect in the short and medium term.…”
Section: E T T E R T O T H E E D I T O Rmentioning
confidence: 99%
“…We too were interested in understanding how sleep management might be helpful for people with pain and synthesized the evidence available to investigate the effect of hypnotic medicines at reducing pain intensity postoperatively (O'Hagan et al, 2020). The systematic review results show that there was moderate-quality evidence that the hypnotic medicine zolpidem, a z-drug, administered in the postoperative period had an analgesic effect in the short and medium term.…”
Section: E T T E R T O T H E E D I T O Rmentioning
confidence: 99%
“…In addition, patients will be given 400 mg celecoxib 2 h after surgery and an additional 200 mg 6 h after that. Thereafter, 200 mg is administered twice daily until postoperative day 7 [13].…”
Section: Perioperative Analgesiamentioning
confidence: 99%
“…A medial parapatellar approach will be used to implant a cemented posterior-stabilized prosthesis (Triathlon Systems; Stryker Orthopedics, NJ). Drain will not be used to allow for unrestricted movement [13]. A clinically prescribed postoperative rehabilitation program will be followed.…”
Section: Surgical Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Sedatives described in the management of postoperative pain after ACLR, are typically of the nonbenzodiazepine class including agents such as zolpidem that increase the activity of inhibitory gammaaminobutyric acid (GABA) receptors centrally, and α2-adrenergic agonistic agents such as dexmedetomidine. [76][77][78] Patients receiving 10 mg of zolpidem nightly for the first week postoperatively after ACLR have been shown to have a 28% reduction in opioid consumption. 77 Similarly, a study explored the use of IA dexmedetomidine when used in conjunction with levobupivacaine, versus IA levobupivacaine alone and concluded that those treated with a combination of dexmedetomidine and levobupivacaine had significantly lower opiate consumption, VAS pain scores, and required less analgesics overall in the postoperative period.…”
Section: Sedatives Gabapentinoids Corticosteroidsmentioning
confidence: 99%